2015
DOI: 10.1371/journal.pone.0142396
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Differences in Placenta and Endometrium between Normal and Intrauterine Growth Restricted Pig Fetuses

Abstract: Uteroplacental tissue plays a key role in substance exchanges between maternal and fetal circulation, and, therefore, in the growth and development of fetuses. In this study, proteomics and western blotting were applied to investigate the changes of proteome in the placenta and endometrium of normal and intrauterine growth restriction (IUGR) porcine fetuses during mid to late pregnancy (D60, 90, and 110 of gestation). Our results showed that proteins participating in cell structure, energy metabolism, stress r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 44 publications
3
28
1
Order By: Relevance
“…In the current study, placental KI67 expression was decreased, suggesting decreased proliferation, in samples associated with the lightest fetuses compared to the CTMLW at GD45. This supports the work published by Chen et al [ 32 ], which suggested that components of the proliferation pathway were downregulated on a protein level in porcine placental and endometrial samples associated with IUGR fetuses compared to those associated with normal birth weight (NBW) fetuses at GD60, 90, and 110.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the current study, placental KI67 expression was decreased, suggesting decreased proliferation, in samples associated with the lightest fetuses compared to the CTMLW at GD45. This supports the work published by Chen et al [ 32 ], which suggested that components of the proliferation pathway were downregulated on a protein level in porcine placental and endometrial samples associated with IUGR fetuses compared to those associated with normal birth weight (NBW) fetuses at GD60, 90, and 110.…”
Section: Discussionsupporting
confidence: 91%
“…Decreased placental BCL2 expression [ 29 , 30 ], accompanied by increased BAX [ 29 ] expression has been observed in term IUGR placentas compared to those supplying normally-grown infants. In the pig, it has been suggested on a protein level that components of the proliferation pathway are downregulated, accompanied by increased apoptotic stress in placentas associated with IUGR fetuses compared to normal-body weight fetuses at GD60, 90 and 110 [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…The global gene expression profile of the hearts of offspring in this IUGR-rabbit model showed alterations in different pathways, all of which converged to mitochondria, including oxygen homeostasis, mitochondrial respiratory chain (MRC) complex I, oxidative phosphorylation and NADH dehydrogenase activity (10,14). Alternative animal models of IUGR have been developed consisting in carunclectomy, uterine artery ligation, uterine space restriction, caloric restriction or hypoxic conditions, among other procedures, in different species of animals (mainly sheep, pigs or rats models) (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Heart development is different among species (in structure, timing of maturation, morphology, function, etc.).…”
mentioning
confidence: 99%
“…Recently, some "omics" profiles have been carried out in the male brood pouch of the seahorse (Whittington et al, 2015), eggshell membranes of the chick (Cordeiro and Hincke, 2016), and placental tissues in mammals (Balestrieri et al, 2013;Mushahary et al, 2013;Strazzullo et al, 2014;Chen et al, 2015) and in viviparous skinks: Chalcides ocellatus and Pseudemoia entrecasteauxii (Brandley et al, 2012;Griffith et al, 2016b). In these skinks, pregnancy is a clearly multistep process.…”
Section: Discussionmentioning
confidence: 99%